2017
DOI: 10.7860/jcdr/2017/22741.9258
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Apolipoprotein A1, B100 and Lipoprotein (a) in Controlled and Uncontrolled Diabetic Patients and in Non-Diabetic Healthy People

Abstract: Introduction: Diabetes Mellitus (DM) is always a multifactorial metabolic disorder having a wide range of abnormalities in carbohydrate, lipid and protein metabolism. Dyslipidemia is a natural process of DM causing abnormal variations of different lipoproteins and it is one of the significant risk factors for Cardiovascular Disorder (CVD). There is a need to closely evaluate newer approaches in case of DM because even if dyslipidemia is treated, there is always a risk of CVDs in DM patients because of the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…Isolated Triglyceride levels shows a positive correlation with age (r=0.219; p= 0.000), Gender (0.076; p=0.008), HbA1C (r=0.104; p=0.00) as shown in Multifactorial disorders such as diabetes present a wide range of lipid abnormalities. Among T2DM individuals, the incidence of hyper triglyceride was high when compared to other lipid abnormalities (14,15). The current study highlighted the existence of significant correlation among HbA1C, Gender, and age with hypertriglyceridemia.…”
Section: Resultssupporting
confidence: 49%
“…Isolated Triglyceride levels shows a positive correlation with age (r=0.219; p= 0.000), Gender (0.076; p=0.008), HbA1C (r=0.104; p=0.00) as shown in Multifactorial disorders such as diabetes present a wide range of lipid abnormalities. Among T2DM individuals, the incidence of hyper triglyceride was high when compared to other lipid abnormalities (14,15). The current study highlighted the existence of significant correlation among HbA1C, Gender, and age with hypertriglyceridemia.…”
Section: Resultssupporting
confidence: 49%
“…This is not surprising, as SEC method isolates nanoparticles based on size and many lipoproteins (LDLs, VLDLs and chylomicrons) and also larger protein aggregates 37 are in the same size-range as EVs 38 . Moreover, lipoproteins are approximately 10 7 -fold more abundant in human blood plasma than EVs 7 , 9 , with reported concentrations of ApoA1 and ApoB100 in healthy adults of 189.11 × 10 4 ng/mL and 147.25 × 10 4 ng/mL, respectively 39 . We have shown that high concentrations of ApoA1 (median value: 1.1 × 10 4 ng/mL) and ApoB100 (median value: 2.6 × 10 4 ng/mL) are present in the sample even after enrichment of EVs with SEC.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a multifactorial disorder having a wide range of lipid abnormalities. In type 2 diabetes mellitus, there is an increased incidence of hypertriglyceridemia as compared to other lipid abnormalities [ 16 - 17 ]. This study evaluated the correlation between glycated hemoglobin (HbA1c) and triglycerides level and the results showed that there is a significant correlation between high HbA1c and high triglyceride.…”
Section: Discussionmentioning
confidence: 99%